Relational measurements and uncertainty. (November 2016) - Krechmer, Ken
Graphical abstract: Highlights: Explains the dicotomy between quantum measurements and classical metrology. Derives the uncertainty relations using classical physics. Presents a measurement model which defines calibration and sampling. Reproduces Ozawa's (2003) quantum physics results. Abstract: In representational measurement theory, the current theory of all measurements, calibration and sampling processes are assumed to be a linear transformation of the coordinate system, of no effect. In this paper calibration and sampling are shown to be independent non-linear processes which do change measurement results. Relational measurement theory is developed to include calibration and sampling. The measurement changes caused by calibration and sampling are proven to be equal to the quantum measurement disturbance described by the universal uncertainty relation which has been verified by experiments. Therefore relational measurement theory explains the measurement disturbance in quantum mechanics.